THE USE OF PICTURE STORYBOOKS FOR IMPROVING READING COMPREHENSION AMONG FIFTH-GRADE STUDENTS - Pratama, Hadi (Raden Intan State Islamic University of Lampung, Indonesia, 2025)
This classroom action research investigated the use of picture storybooks combined with guided reading strategies to improve the reading comprehension of fifth-grade EFL learners at SDN 1 Sedampah Indah, Lampung. The study was conducted in two cycles, each comprising planning, action, observation, and reflection stages. Data were collected through pre- and post-tests, classroom observations, interviews, teacher reflections, and analysis of student work. Quantitative findings revealed significant improvements in reading comprehension, with mean scores rising from 54.82 in the pre-test to 72.36 in the final post-test. The largest gains occurred in inferential comprehension, supported by qualitative evidence showing increased student engagement, confidence, and participation. Instructional refinements—such as explicit vocabulary pre-teaching, guided questioning, and the inclusion of culturally relevant storybooks—were identified as key factors in enhancing comprehension. Challenges included limited access to suitable materials and time constraints for extended discussions. The results indicate that picture storybooks, when implemented with structured support and reflective teaching practices, can significantly improve comprehension skills and foster a more inclusive and motivating classroom environment for rural EFL learners. Overall, this study reinforces that picture storybooks, when implemented with pedagogical planning and contextual adaptation, can serve as a powerful tool for developing comprehension skills, fostering motivation, and creating inclusive literacy instruction in rural EFL classrooms. The findings offer practical implications for teachers, curriculum developers, and education authorities seeking to improve literacy outcomes in similar educational contexts